Effectiveness of the developed instrumentation system on the vehicle tractive performance measurement - Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Hossain, Altab (Universiti Malaya, 2007)
The effectiveness of the developed automation system on the vehicle was verified with the validated mathematical model. The vehicle’s tractive efforts recorded with the installed developed automation system in the range of 40 to 64 % of the vehicle gross weight and 47 to 67% of the vehicle dry weight, represent the high effectiveness of the torque transducer. Furthermore, the recorded vehicle’s maximum tractive effort at the slippages in the range of 6 to 12% also represents the higher effectiveness of the developed speed transducer. Integrated developed automation system is considered precise and effective from the recorded tractive effort of 62% of the 6 wheeler drive vehicle’s gross weight at 15% slippage.